Meningkatkan Hasil Belajar Matematika Dengan Metode Quipper School Pada Sd Negeri 4 Kaloran - Aisyah, Uud; Ermawati, Elisa; Hajron, Kun Hisnan (Prosiding University Research Colloquium, 2021)
The purpose of this study is to see how using the learning media Quipper School affects elementary school children 4 Kaloran's enthusiasm in learning mathematics. This study's findings were obtained by quantitative approaches, such as interviews with elementary school instructors, such as Ibu Juni Prihatin, S.Pd. Students from SD Negeri 4 Kaloran, a total of 20 students, were the subjects of this study. Only students with a math score of 65-70 on the Mathematics test were chosen as part of the sample. This study used two test tests with an average score of 30.72 for the first test group of 20 students, with the highest score of 40 and the lowest score of 20. The average score for the second test group of 20 students was 48.56, with the highest value being 90 and the lowest being 40. The average value of the two classes' pretests is much below the specified value of 7.5, which is the minimal completeness criterion. According to the calculation data, there were 5 students who had a strong interest in learning mathematics, 9 students who had a sufficient interest in learning mathematics, and 6 students who had no interest in learning mathematics before using themedia Quipper School. In addition, students in the class had an average interest in learning in mathematics classes of 74.3 percent. Using Quipper School means that the increase or success that students achieve is increasing as a result of achieving better grades than before the learning media was given Quipper School, indicating that this method is effective in improving the learning scores of elementary school students in Mathematics.